ANALISIS RASIO KEUANGAN DAERAH UNTUK MENILAI KENERJA KEUANGAN DAERAH ( STUDI KASUS PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET KOTA KEDIRI) - Nurdiwaty, Diah; Zaman, Badrus (Faculty of Economics and Business, University of Muhammadiyah Malang, 2016)
The purpose of this study was to examine the factors that determine the profitability of the banks of the largest commercial banks nationwide in Indonesia for the period 2010-2014. Based on the prescribed criteria, banks selected as samples were Bank Central Asia, Bank Negara Indonesia and Bank Mandiri. The dependent variable in this study is profit. The independent variables consist of liquidity risk, credit risk and efficiency. The analytical tool used is multiple linear regression analysis. The results showed that the liquidity risk of significant and positive impact on profits. Meanwhile, credit risk and efficiency significant and negative effect on profits. Concurrently, liquidity risk, credit risk and efficiency has a significant effect on earnings.